Leadership Style Affects Nursing Quality Improvement: Meta-Analysis Study - Nurjaman, Iman; Saparlina, Ina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Background: Leadership style can have a significant influence on improving the quality of nursing in various nursing service contexts. Improving the quality of nursing is important to improve the standard of nursing services so that it can provide more effective, efficient, safe, and quality care to clients. There have been many studies that examine the influence of leadership style on improving the quality of nursing. Aim: Based on existing research, it is necessary to conduct a meta-analysis study to obtain a summary effect size between leadership style and nursing quality improvement. Design: Meta-analysis. Method: The protocol in this study uses review and dissemination and the Joanna Briggs Institute (JBI) Guidelines as guidelines in assessing the quality of correlation meta-analysis research. Article sources are collected through Scopus, Science Direct, PubMed, and Google Scholar, according to predetermined criteria. Data analysis using the help of the JASP 0.18 application. Results: A total of 12 research artifacts obtained a positive and significant influence on leadership style and improving nursing quality, summary effect size (rRE = 0.662) is the maximum size in the high category. Conclusion: This research, of course, has proven consistency and strengthened the theory or findings of previous researchers that with meta-analysis studies can provide convincing and effective information about the influence of these two variables. Quality or relationship between leadership styles to improve nursing quality on an ongoing basis through commitment, teamwork, and strong leadership.